A new gold nanoparticles modified screen printed paper card based microfluidic device - Hayatu, Salamatu; Abdul Audu, AbduRahman; Ladan, Magaji; Yusof, Nor Azah (Malaysian Analytical Sciences Society, 2023)
This work offers a novel platform for the straightforward and low-cost manufacture of paper microfluidic devices known as gold nanoparticles modified screen printed paper electrode AuNPs/SPPE. The component can function as an electrochemical cell as well as a microfluidic device. Different paper cards were evaluated for hydrophobicity, and metallic gold card was selected due to its superior hydrophobic properties. Thus, waxing and other pretreatment steps are eliminated. The AuNPs/SPPE was created by screen printing on metallic gold card using commercial silver ink. Working electrode was modified using synthesized gold nanoparticles (AuNPs). The presence and widespread distribution of Au particles are shown by SEM and EDX study. The conductivity and resistivity study shows good conductance. The device was applied in tramadol detection, tramadol was studied electrochemically using cyclic voltammetry technique, where it was oxidized at 0.1 to 0.3 volts. Positive results obtained from electrochemical investigation suggest good and promising future applications.